Factors Related to Self-Breast Examination in Fertile Women in the Work Area of Cimahi Tengah Public Health Center Indonesia - Marlina, Dini; Waslia, Dede (KnE Life Sciences, 2021)
Breast cancer is a major problem for women’s health in the world, especially in developing countries that have limited resources such as in Indonesia. The reason is because of the lack of an effective screening program to detect conditions before cancer or cancer at an early stage including treatment before further invasive processes. Early detection of breast cancer needs to be done to reduce mortality. Breast selfexamination (BSE) can find breast cancer up to 75-85% if done routinely. Willingness to do breast self-examination (BSE) is one form of behavior that is influenced by many factors including predisposing factors, supporting factors and reinforcing factors. The research aimed to determine factors associated with breast self-examination (BSE) in Fertile Age Women in the Cimahi Middle Health Center Working Area 2017. This study was conducted using quantitative method with cross sectional approach. The population in this study were Fertile Age Women in the working area of the central Cimahi Community Health Center with a sample of 120 people using random sampling techniques. Data collection was carried out through direct interviews using a questionnaire. The results of the study concluded that of the 120 respondents, the majority of respondents (74.2%) did breast self-examination (BSE). Predisposing factors related to BSE are Menarch (Pvalue 0,000), history of breast cancer (Pvalue 0.002), parity (Pvalue 0.001) and knowledge (Pvalue 0.001). The enabling factors related to BSE are information sources (Pvalue 0.006), the availability of information media (Pvalue 0.012), and the availability of facilities that support the BSE (Pvalue 0,000). The reinforcing factors associated with BSE are friend support (Pvalue 0,000), husband / family support (Pvalue 0,000), and support of health workers (Pvalue 0,000). Fertile Age Women mostly do breast self-examination (BSE). The most related predisposing factor is Menarch, enabling factor is the availability of facilities, while the most related reinforcing factor is husband / family support. It is expected that health workers can improve their skills in early detection of breast cancer through the BSE program so that the discovery of breast cancer cases can be found as early as possible and the provision of information using the media so that the public will be exposed to information easily through the information conveyed. Keywords: breast cancer, early detection, breast self-examination, Fertile Age Women, behavior